Device profile of the XIENCE V and XIENCE Sierra stents for the treatment of coronary artery disease: an overview of safety and efficacy. (3rd May 2020) - Mitsis, Andreas; Valgimigli, Marco
ABSTRACT: Introduction : Coronary angioplasty with the use of stents transformed the percutaneous treatment of coronary artery disease. First-generation drug-eluting stents reduced the risk of restenosis but carried a threat of late stent thrombosis. Second-generation drug-eluting stents resolved these issues and have proven so far very good safety and efficacy performance. Areas covered : This article aims to describe the new XIENCE® Sierra everolimus-eluting coronary stent system, to analyze the available data so far with regards to the safety, the effectiveness, and the overall clinical performance of the device and to seek future perspectives. Expert opinion : XIENCE® Sierra everolimus-eluting coronary stent carries all the positive features of the precursor stents of the XIENCE® family and brings an ultra-low crossing profile which further increases deliverability and flexibility. CoCr-everolimus-eluting stents are among if not the most extensively investigated coronary stents and have demonstrated over the years a consistently remarkable low risk of acute, subacute, late, and very late stent thrombosis and are considered a trustworthy device in the interventional management of complex coronary artery disease.